Preferensi Masyarakat Terhadap Gadai Syariah (Studi Kasus Gadai Emas BRI Syariah Yogyakarta) - Muhammad Aris Safi’i (Jurnal Hukum Islam, 2016)
Product diversification Islamic bank as one of services can encourage the emergence of customer preference towards Islamic Bank, and one of the products is the pledge of gold. The diversity of the people’s choice for a product make marketing as the most important part, and the important stage of marketing is to analyze the behavior of customers. Through this research, we can know “the factors affecting customer referrers against pawn of gold in BRI Syariah Yogyakarta branch”. The author attempted to examine and analyze five (5) factors; trust, religious, profit, service, and promotion. This study is a field research with qualitative methods based on primary and secondary data. The sampling method used purposive sampling, in which the data were collected through interviews to the management and customers, bank document tracking and deployment questionnaire to the respondent. The data analysis technique used is the analysis of frequency analysis which test the validity and reliability of the data questioner. The result found there were five factors in order are as follows: religious and trust get a high score, profit, service, and promotion.